2021
DOI: 10.3390/membranes11090719
|View full text |Cite
|
Sign up to set email alerts
|

Use of Essential Oils for the Control of Anthracnose Disease Caused by Colletotrichum acutatum on Post-Harvest Mangoes of Cat Hoa Loc Variety

Abstract: Anthracnose disease caused by Colletotrichum spp. makes heavy losses for post-harvest mangoes of Cat Hoa Loc variety during storage, packaging, and transportation. The synthetic fungicides are commonly used to control the disease, but they are not safe for consumers’ health and environment. This study was aimed to investigate the use of essential oils (EOs) as the safe alternative control. Pathogen was isolated from the infected Cat Hoa Loc mangoes and identified by morphology and DNA sequencing of the ITS reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
(82 reference statements)
1
18
0
Order By: Relevance
“…It was recently reported that essential oil of cinnamon bark, basil, and lemongrass inhibited C. acutatum growth in vitro with the minimum inhibitory concentrations of 1.6, 4, and 12 mL L −1 , respectively. In addition, basil essential oil suppressed anthracnose development in ‘Cat Hoa Loc’ mango inoculated with C. acutatum , while cinnamon bark and lemongrass essential oil damaged the fruit skin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that essential oil of cinnamon bark, basil, and lemongrass inhibited C. acutatum growth in vitro with the minimum inhibitory concentrations of 1.6, 4, and 12 mL L −1 , respectively. In addition, basil essential oil suppressed anthracnose development in ‘Cat Hoa Loc’ mango inoculated with C. acutatum , while cinnamon bark and lemongrass essential oil damaged the fruit skin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The required dose for PE was higher than that of L. scaberrima and basil essential oil, likely due to the differences in an experimental setting and major constituents. In in vitro fungicidal assays, we cultured C. gloeosporioides at 28 °C for 7 d, whereas Regnier et al [ 22 ] conducted the experiment at 23 °C for 6 d. In the in vivo trials, we placed the fruit at 20 °C for 14 d. In contrast, Regnier et al [ 22 ] and Danh et al [ 23 ] sterilized the fruit with 70% ethanol, inoculated the fruit with the pathogens, and observed fungal growth for 6 d and 3–7 d after storage, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oils from Ocimum spp. were able to inhibit the fungi causing the post-harvest diseases of the tropical fruits [10,13,14,101]. This also includes Colletotrichum spp., the fungus that causes anthracnose disease in common tropical fruits.…”
Section: Post-harvest Applicationsmentioning
confidence: 99%
“…Ocimum sp. (methyl chavicol and linalool) antifungal agent (MIC = 4 µL/mL) [13] Monilinia laxa (brown rot and grey mould rot of stone fruits)…”
Section: Post-harvest Applicationsmentioning
confidence: 99%
See 1 more Smart Citation